Exosomes in Cancer Nanomedicine and Immunotherapy: Prospects and Challenges. Issue 7 (July 2017) - Syn, Nicholas L.; Wang, Lingzhi; Chow, Edward Kai-Hua; Lim, Chwee Teck; Goh, Boon-Cher
Abstract : Exosomes (versatile, cell-derived nanovesicles naturally endowed with exquisite target-homing specificity and the ability to surmount in vivo biological barriers) hold substantial promise for developing exciting approaches in drug delivery and cancer immunotherapy. Specifically, bioengineered exosomes are being successfully deployed to deliver potent tumoricidal drugs (siRNAs and chemotherapeutic compounds) preferentially to cancer cells, while a new generation of exosome-based therapeutic cancer vaccines has produced enticing results in early-phase clinical trials. Here, we review the state-of-the-art technologies and protocols, and discuss the prospects and challenges for the clinical development of this emerging class of therapeutics. Trends: Exosomes are extracellular cell-derived phospholipid nanovesicles that function as signalosomes, transmitting prodigious amounts of bioactive molecules to specific recipient tissues. Their intriguing endogenous functionalities have galvanized momentous efforts to exploit them as novel anticancer therapeutics. Exosomes may offer a tractable, bioinspired system for targeted drug delivery, which could improve the therapeutic indices of conventional cytotoxic chemotherapeutic agents, and help to realize the enormous potential of gene therapy in oncology. Owing to their immunomodulatory potential, exosomes may also be deployed in innovative immunological approaches to activate adaptive and innate effector cell-mediated anticancer immunosurveillance.